Decrease in Stigma Towards Mental Illness in Portuguese Medical Students After a Psychiatry Course - Vilar Queirós, Rita (2021)
Introduction: Stigma towards mental illness is considered a key obstacle to the provision of medical care to psychiatric patients. This is not only present in the general population but also among healthcare professionals. Therefore, medical students could be a target population for stigma prevention measures. The aim of this study is to assess the evolution of the attitudes of medical students from the Faculty of Medicine of the University of Coimbra towards psychiatric patients, before and after attending Psychology and Psychiatric courses.Material and Methods: Students from the third and fourth years of the integrated Master’s degree in Medicine in the Faculty of Medicine of the University of Coimbra were asked to complete four questionnaires. The surveys were distributed before and after the attendance of the courses.Results: There was a statistically significant decrease of the stigma scores (p = 0.025) between the two measurements (38.16 initially, 36.72 on the second moment). The baseline level of stigma was found to be negatively associated with empathy (rP = -0.477) and with the type of personality, with higher levels of openness to new experiences being associated with lower levels of initial stigma (rP = -0.357).Discussion: Overall, the students’ attitudes towards patients with mental illness were positive, with a decrease of the stigma value from the first to the second semester. This corroborates the hypothesis that education and contact with people with a mental condition could shape positive changes in attitudes and discrimination against those patients.Conclusion: Our results emphasise the importance of implementing programs inside medical schools in order to reduce stigma among future doctors.